Right to Be Forgotten in Spent Criminal Convictions - Faisal, Kamrul (My University, 2020)
Individual’s past personal data proved to have unimaginable impact on his or her present and the future in particular the spent criminal convicts’ faux pas committed in the past might trap oneself to an unchangeable present and the future. This impact is greater in this advanced communication technological era when personal information is just one click away through search engines and potential victims might be reformed sinners, minor offenders, adolescents and prospective employees who want to represent themselves in consistent with the respective societal interests and values. A successful exercise of right to be forgotten, a derivative of data protection privacy right under GDPR can aid in characterizing this aspiration of reintegration through a new inception of reformed life by restricting the access of the concerned information online. Since access to information is an aspect of right to freedom of expression, both need to be weighed against each other to prioritize one in each case. The established concept and jurisprudence of RTBF does not guarantee any spent criminal convict to erase the relevant history permanently, rather only to delink the hyperlinks from the Internet search engines which makes the retrieval difficult. Even, to reach that far, a series of certain balancing principles suffice in motion which need to be evaluated to weigh between RTBF and free expression, such as, whether the process at issues is a lawful or unlawful one, data subject is a public or private figure, and proportional processing or privacy interests in motion. These characteristics make a RTBF application non-exclusive in nature since it cannot be guaranteed to spent convicts as admittedly, it must face the risk of rejection.
Keywords: Data protection, Right to be forgotten, Freedom of expression, Spent convicts, Publication interest, Privacy interest, Internet, GDPR, Google Spain.